Early bilirubinemia after allogeneic stem cell transplantation: an endothelial complication - Dai, Hao; Penack, Olaf; Radujković, Aleksandar; Schult, David; Majer-Lauterbach, Joshua; Blau, Igor-Wolfgang; Bullinger, Lars; Jiang, Sihe; Müller-Tidow, Carsten; Dreger, Peter; Luft, Thomas (Bone marrow transplantation, 2021)
Hyperbilirubinemia occurs frequently after allogeneic stem cell transplantation. Causes include primary liver damage and endothelial complications as major contributors. Here, we have investigated the impact of early bilirubinemia (EB) on posttransplant outcomes. Maximum total bilirubin levels (days 0-28) were categorized using maximally selected log rank statistics to identify a cut off for the endpoint non-relapse mortality (NRM) in a training cohort of 873 patients. EB above this cut off was correlated with NRM and overall survival (OS) and with pre- and posttransplant Angiopoietin-2, interleukin (IL)18, CXCL8 and suppressor of tumorigenicity-2 (ST2) serum levels, and the endothelial activation and stress index (EASIX). Clinical correlations were validated in a sample of 388 patients transplanted in an independent institution. The EB cut off was determined at 3.6 mg/dL (61.6 µM). EB predicted OS (HR 1.60, 95% CI 1.21-2.12, p < 0.001), and NRM (CSHR 2.14; 1.28-3.56, p = 0.004), also independent of typical endothelial complications such as veno-occlusive disease, refractory acute graft-versus-host disease, or transplant-associated microangiopathy. However, EB correlated with high Angiopoietin-2, EASIX-pre and EASIX-day 0, as well as increased levels of posttransplant CXCL8, IL18, and ST2. In summary, EB indicates a poor prognosis. The association of EB with endothelial biomarkers suggests an endothelial pathomechanism also for this posttransplant complication.